SOCIAL-ECOLOGICAL SYSTEM OF MANGROVE REHABILITATION INITIATIVES: A COMPREHENSIVE STUDY IN BREBES REGENCY, CENTRAL JAVA: SISTEM SOSIAL-EKOLOGI INISIATIF REHABILITASI MANGROVE: STUDI KOMPREHENSIF DI KABUPATEN BREBES, PROVINSI JAWA TENGAH - Fredinan Yulianda; Sulistiono Sulistiono; Hery Gunawan Daulay; Luky Adrianto (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2026)
Mangrove ecosystem rehabilitation based on a social-ecological systems (SES) approach is a holistic analysis that integrates ecological and social dimensions in coastal restoration and conservation efforts. The success of this rehabilitation is influenced by the complex interaction between environmental biophysical factors and governance dynamics, including government policies, public participation, and local wisdom practices. This study aims to map and analyze the dynamics of SES in a mangrove rehabilitation program. Data were collected using the rapid rural appraisal (RRA) method from June to August 2024. The study results were formulated into a conceptual model of the basic SES network for mangrove rehabilitation in Brebes Regency. The identified network model consists of 85 components (nodes) and 141 causal relationships (links). The research findings indicate that the managing resource actors (RAs) act as the central component (core of the network) that drives the sustainability of rehabilitation activities in the coastal areas of Brebes Regency. The synergy of roles between actors within this SES framework is crucial in increasing the effectiveness and sustainability of the program. It is expected to optimize ecological functions and provide socio-economic added value for coastal communities.